Clinical Features of a Group of Adolescents Diagnosed with Primary Hyperparathyroidism - Gunbey, Omer; Paksoy, Firdevs Dilara; Acar, Nurdan Yildirim; Okdemir, Deniz; Esen, Ihsan (Galenos Publ House, 2025)
Introduction: Primary hyperparathyroidism (PHPT) is a rare disease in children. There are a limited number of publications on pediatric PHPT. In this study, we present the clinical characteristics of a group of children with PHPT. Materials and Methods: The hospital records of seven adolescents diagnosed with PHPT and who underwent surgery at our clinic between 2013 and 2023 were retrospectively reviewed. Results: The study group consisted of seven adolescents, three of whom were girls, with a median age of 14 years (range: 13-17). The most common presenting symptom was myalgia (3/7). One patient with abdominal pain was diagnosed with acute pancreatitis. Three patients had nephrolithiasis secondary to hypercalcemia. Ultrasonography detected adenomas in five patients (71%). Scintigraphic imaging revealed isolated parathyroid adenomas ranging from 0.5 to 2.0 cm in size in all patients. The most common lesion location was the lower part of the right thyroid lobe (3/7). All patients underwent surgical excision of the parathyroid adenoma. Preoperative median calcium level was 12.0 mg/dL (10.6-13.1), and median parathyroid hormone (PTH) level was 340 pg/mL (98-803). Postoperatively, median calcium level decreased to 8.6 mg/dL (8.3-9.1), and median PTH level decreased to 38.3 pg/mL (12.2-73.0). No postoperative complications were observed. Pathology results confirmed parathyroid adenoma in all cases. All patients remained in remission after at least six months of follow-up. Conclusion: This study indicates that children with PHPT are often diagnosed based on non-specific symptoms. Isolated parathyroid adenomas detected through imaging can be successfully treated with surgery.
Primer Hiperparatiroidizm Tanılı Bir Grup Adolesanın Klinik Özellikleri
Keywords: Adolescent; hypercalcemia; parathyroid adenoma; primary hyperparathyroidism